Quantifier pour manager. L’émergence des paiements pour services environnementaux au sein des politiques publiques environnementales françaises - Rémy Petitimbert (Développement Durable et Territoires)
Public policies have known a new managerial approach growth promoted by the cognitive and practice framework of New Public Management. This development has empowered the institutionalization of efficiency and effectiveness indicators in public sector’s practices. In fact, it seems that ecosystem services and payments for environmental services register in this new philosophy. Drawing on this, this paper proposes to consider the production’s conditions of tools and monetary evaluation procedures in environmental policies. Finally, the article argues that this procedures contains and disseminate a reduction point of view about the biodiversity value.